AB0022 INTERRELATIONS OF INCREASED AXIAL SPONDYLOARTHRITIS ACTIVITY AND THE SERUM CONCENTRATION OF IMMUNOGLOBULIN A TO CD74 WITH GENETIC POLYMORPHISMS OF INTERLEUKIN 17 ALLELES. (2nd June 2020) - Vasilenko, E.; Korolev, M.; Lapin, S.; Kholopova, I.; Dadalova, A.; Mazurov, V.; Gaydukova, I.
Abstract : Background: Genetic predisposition takes one of the main parts at pathogenesis of axial spondyloarthritis (axSpA). Currently, HLA-B27 is a single genetic marker that used in classification criteria of axSpA. However, the presence of HLA-B27 does not affect the activity of the disease. An alternative biomarker of axSpA activity could be an immunoglobulin (Ig) A antibody to an invariant chain peptide associated with class II human leukocyte antigen (HLA) (anti-CD74). Objectives: The goal is to determine genetic polymorphisms of IL17 alleles prevalence in patients (pts) with axSpA and their interrelations with the disease activity and concentration of IgA to CD74. Methods: In 48 patients with a reliable diagnosis of axSpA, aged 18 to 69 years ASDAS, BASDAI, BASFI were calculated. The polymorphisms of alleles of interleukin (IL)-17A197 a/g, IL-17F7 histidine (His)/arginine (Arg), IL-17F11139 c/g, HLA-B27 were evaluated. Serum concentration of IgA to CD74 was measured (the normal reference interval according to the instructions for the laboratory kit for serum IgA to CD74 is 0-12.0 U/L). Results: The mean age of pts was 45.1±14.2 years, male 72.9%, BASDAI 2.99±0.28, ASDAS 2.29±0.16 (Cronbach's alpha for the scales – 0.830), IgA to CD74 16.9±11.0 mg/L. The most often found polymorphisms of interleukin-17 alleles demonstrated in table 1 . Exceeded levels of IgA to CD74 were identified at 96 pts (70.1%). The factor analysis showed a relationship between ASDAS (R=0.857), BASDAI (R=0.842), BASFI (R=0.857) and level of IgA to CD74 (R=0.667), (table 2 ). An increase in the factor load indices for IgA to CD74 (R=0.925) was established, provided that the IL-17F genotype is homozygous for the his / arg allele (R=0.544). The genotypes IL-17F his/his showed an inverse interrelation with the increase in serum IgA to CD74 level (R=-0.421). Conclusion: Serum concentration of IgA to CD74 exceeded normal reference level in axSpA patients in 70.1% of cases that was associated with ASDAS and BASDAI levels. Presence of heterozygote IL-17F polymorphism in his/arg allele was associated with increasing serum concentration of IgA to CD74 and with increased disease activity (ASDAS and BASDAI). Decreasing of serum IgA to CD74 concentration, less axSpA activity (ASDAS and BASDAI) were found in patients with presence of heterozygote IL-17F polymorphism in his/his allele. Disclosure of Interests: Elizaveta Vasilenko: None declared, Maxim Korolev: None declared, Sergey Lapin: None declared, Irina Kholopova: None declared, Anna Dadalova: None declared, V Mazurov: None declared, Inna Gaydukova Grant/research support from: JSC BIOCAD, Speakers bureau: Pfizer, Novartis, AbbVie, JSC BIOCAD, Сelgene, MSD, Sanofi